(untitled) (Jurnal Mekanikal, 2018)
Limited supply of petroleum resources, global warming issues and increasing yearly prices of petroleum in the present time, motivated scientists to find new alternative and cheap energy resources. Utilization of edible oil like vegetable oils as fuel actualized the competition between human needs in food and non -food applications. Also, the utilization of non-edible seed oils as renewable sources of fuel are costly due to the planting and production cost of the crude oils. In this study, the physical properties of crude palm oil (CPO), refined bleached deodorized (RBD) palm oil, waste cooking oil (WCO) and their methyl esters, has been investigated and characterized. Secondly, comparison was made using conventional method and microwave irradiation method of production of biodiesel, looking at different microwave exit powers, reaction time and reaction temperatures. The waste cooking oil (WCO) methyl ester characterization was done according to the ASTM method and was compared with published data. Generally, the flash point of this oil was reduced to 131ºC in its methyl ester form which is safe to be stored. Another result was the calorific value of the WCO methyl ester. It was 40,870 kJ/kg, which was slightly higher than its unprocessed form but still lower than diesel fuel. The cloud point and pour point of WCO methyl ester were lower than the CPO methyl ester but slightly higher than RBD methyl ester which are 13ºC and 9ºC respectively. The kinematic viscosity at 40ºC was 3.019 cSt, which was comparable with conventional diesel. Waste cooking oil’s density (0.886 kg/liter) was slightly higher than conventional diesel. The results showed that microwave irradiation decreases the reaction time dramatically from using conventional methods of 60 to 180 min to only 5 to 9 min.